Evaluation of Drainage System on Public Road in Front of Sidoarjo Religious Court Office Class 1A - Windya Yunesti Ernitasari; Budi Witjaksana; Andi Patriadi (CV. Proaksara Global Transeduka, 2024)
Flooding in front of the Sidoarjo Class 1A Religious Court Office road happens frequently during the rainy season. It disrupts traffic and damages the roads. Flooding is caused by the condition of the drainage channels, which are not performing efficiently due to sediment barriers such as garbage, and some channels appear to be damaged. The existing channels can no longer accommodate the water discharge caused by the rain, thus water overflows from the drainage channels, flooding the main road. These conditions show the importance of handling drainage problems. One of the ways that can be taken is to evaluate the capacity of existing drainage channels.In this study, the evaluation of drainage channel capacity was carried out using the Hydrological and Hydraulics Analysis method. The purpose of this study was to determine the amount of drainage channel storage capacity required to resolve flooding. The results of this study showed that the design rainfall obtained based on the Log Pearson Type III method was 116.583 mm/day with a 5-year return period. The design flood discharge in channel T1 was 0.717 m3/second, while the capacity of the existing tertiary channel T1 = 0.009 m3/second, so the discharge that overflows from the existing channel T1 was 0.708 m3/second. The capacity of the secondary channel S1 was 2.604 m3 /second, whereas the capacity of the primary channel P1 was 43.043 m3 /second. The capacity of the T1 channel was known to be unable to accommodate the design flood discharge. Therefore, alternative treatments were required to ensure that the T1 channel could accommodate the designed flood discharge.